Effect of pleurotus sajor-caju extract on liver enzymes and histological changes in hypercholesterolemic-induced rats - Mohammad, Siti Hajar (2013)
Hypercholesterolemia is a condition where high cholesterol levels are present in the blood. It has been associated with fatty infiltration in the liver which may progress to cirrhosis and hepatic steatosis. Epidemiology study demonstrated that 60% of Malaysians with slightly high in cholesterol levels have NAFLD. Therefore, as the incidence of hypercholesterolemia and other related health problems has been increasing around the world including Malaysia, this preliminary study aimed to find the alternative treatment by using natural substances known as Pleurotus sajor-caju (PSC). PSC is one of the Pleurotus spp. which has been reported to have low calories and fat but rich in proteins and dietary fibers and was proven to have antihyperlipidemic and hepatoprotective activity. In the present study, rats treated with 100 mg/kg of PSC for a month was found to have an effect on the liver enzymes activities since plasma ALP concentration in this group showed a significant reduction (P < 0.05) and a higher percentage reduction (66.01 %) as compared to 20 mg/kg-PSC and 200 mg/kg-PSC treatment groups. However, this finding cannot be categorized as a significant finding as ALP reduction was also observed in HPC control group. Plasma AST and AL T only showed a mild increased by 35.04% and 15.00% respectively in 100 mg/kg-PSC treatment group and there was no significant increased (P > 0.05) found in these both AST and AL T concentrations. Atorvastatin treatment also showed reduction in ALP enzymes but no significant reduction (P > 0.05) as compared to 100 mg/kg-PSC treatment group. On the other hand, plasma AST and AL T in 20 mg/kg of atorvastatin treatment were increased in percentage by 275.97% and 112.50% respectively and this may indicate the adverse effects of statin in term of elevation of plasma enzymes activities. On the histological part, there was no significant finding in the micrograph study between treatment and HPC liver rat. The micrograph of HPC rat liver treated with I 00 mglkg PSC only showed smooth and clear surface of hepatocytes compared to HPC group. In addition, a practical, simple and cheap method of dietatical model for inducing hypercholesterolemia in rats has been successfully developed by using 32 g of ghee per 68 g of rat pellet.